Analysis of Gait Dynamics of ALS Disease and Classification of Artificial Neural Networks - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2018)
In this study, a gait device was used for gathering data.A group comprising control group and ALS patients was requested to walk using this device.Gait signals of the control group individuals and ALS patients taken from their left feet were recorded by means of the sensors sensitive to the force which was placed to the device. Spectral and statistical analyses of these signals were made.The results obtained from these analyses were used for making classification with Artificial Neural Network.In consequence of the classification, the individuals with ALS disease were diagnosed accurately with an average rate of 82 %.In the study, the signals taken from left foot of 14 normal individuals and 13 ALS patients were analyzed.
Keywords: ALS Disease; Artificial Neural Nets; Gait Dynamics Analysis; Piezo Electric Sensors; Sound and Vibration; AMYOTROPHIC-LATERAL-SCLEROSIS; PERSPECTIVE